Evaluation of Coal Mining Safety Management Information Sytem Based on the Internet of Things - Zhu Jianjun; Li Mingxing (Institute of Advanced Engineering and Science, 2013)
In this paper, we put forward three-level indicators and 13 secondary indicators via Delphi method. We improved the new fuzzy synthetic evaluation method from the aspect of coal-mining information management. After a comprehensive evaluation, 72.28% of people believed that security levels of Huaibei Mining Group belonged to good & moderate one, and 27.72% of people held that security status of Group was poor & very poor condition on the basis of comprehensive evaluation. Therefore, security management information system in Huaibei Mining Group belonged to the middle level. By using the new indicators and research method, the countermeasures were given to improve safety management on the basis of the internet of things. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3433